1 Analisis Tingkat Kerusakan Runway Perkerasan Fleksibel Menggunakan Metode Pavement Condition Index (PCI).: Analisis Tingkat Kerusakan Runway Perkerasan Fleksibel Menggunakan Kondisi Perkerasan Metode Indeks (PCI). - Nur Alfira; Andri Irfan Rifai; Yusra Aulia Sari (LPPM Universitas Abdurrab, 2025)
A measure for evaluating the state of road pavements, including airport runways, is the Pavement Condition Index (PCI). Based on the kind, extent, and location of damage, PCI offers an unbiased assessment of the degree of road surface deterioration. Better circumstances are indicated by higher PCI values, which range from 0 to 100. PCI is necessary for runway maintenance management in order to guarantee both flight safety and the effectiveness of airport operations. PCI can be used to assess runway damage, which can be influenced by outside variables like explosive loads, and to schedule necessary maintenance. The study must account for variables that impact the degree of damage, such as the weight of the explosive charge, distance from the point of detonati on, and material quality, PCI has limits when it comes to assessing the structural state of the pavement's deeper layers, despite its considerable advantages in assessing surface damage. Therefore, to give a more comprehensive picture of runway conditions, PCI should be used in conjunction with other techniques such layer thickness testing or load testing. All things considered, PCI is a crucial instrument for managing and maintaining runways to guarantee both aviation safety and efficient airport operations.